Analisis Kesesuaian Kualitas Air Minum Tirtanadi IPAM Hamparan Perak Dengan Baku Mutu Permenkes No. 2 Tahun 2023 - Syafa Rangkuti, Nur Ashilah; Br Ginting, Nurkholisah; Rizka Fadilla, Septiani; Anindya, Nazla; Damanik, Kemala Sari; Arrazy, Syafran (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Drinking water quality needs to be analysed because it directly affects public health and environmental sustainability. Water that does not meet quality standards can cause pollution and health problems, so regular monitoring is essential to ensure the effectiveness of treatment processes and the safety of water for consumption. PERUMDA Tirtanadi IPAM Hamparan Perak, as a drinking water service provider, is responsible for maintaining treated water quality according to applicable standards. This study aims to analyse the quality of treated drinking water at IPAM Hamparan Perak based on physical and chemical parameters and to assess its compliance with the quality standards set by the Indonesian Ministry of Health Regulation (Permenkes) No. 2 of 2023. The research used a descriptive method with monthly laboratory test data from the reservoir unit. Samples were taken from treated water stored in the reservoir, and the results were analysed descriptively by comparing them to drinking water quality standards. The findings showed that all physical parameters (turbidity, colour, odour) and chemical parameters (pH, residual chlorine, Fe, Mn, NO₃, NO₂, Al, Cu, NH₃-N, and SO₄) were below the specified limits. Therefore, the treated water quality at IPAM Hamparan Perak meets drinking water standards and is safe for public consumption.